The Validity of the Bank Credit Channel in the Monetary Transmission Mechanism: VAR Analysis of Participation Banks - Ömer Fazıl Emek (Pamukkale Üniversitesi İşletme Araştırmaları Dergisi, 2023)
The relationship between Islamic banking and monetary policies, and the way this relationship is reflected in the real sector has attracted increasing attention, primarily because of the growing importance of Islamic banking activities. Therefore, a review of the effectiveness of the loan schemes of Islamic banks in Turkey can make a significant contribution to the literature. This study analyzes whether the loan schemes of public and private participation banks operating in Turkey’s dual banking system, are effective. To this end, the study relies on variance decomposition and impulse response function analyses of VAR models compiled from monthly data between 2009:01 and 2020:03. The industrial production index represents economic activity, the interest rate applied to consumer loans, and the total money supply (M1), representing the monetary policy instruments. The model also includes total loans and deposit variables made available for the participation banks, representing the bank loan scheme and other variables, including the nominal exchange rate and consumer price indexes. The study measures the responses of the exchange rate, inflation rate, industrial production index, participation banks’ total loans, and total deposits to one-unit shocks applied to monetary policy and interest rates. The findings from the impulse-response functions indicate that the credit channel in participation banks is partially additional since their total loans and deposits react to monetary policies in certain periods due to changes in money supply and interest rates. However, they cannot reflect this at the production level.